Paper making and paper board making / Pulp and Paper Manufacture: McGraw Hill V3 2nd ed - Macdonald, Ronald G/Franklin, John N
Paper making and paper board making / Pulp and Paper Manufacture: McGraw Hill 676.288 P214e2 V3 2nd ed No. of Copies : 1